Existence or Essence? A Qualitative Study of Islamic Lifestyle of Islamic Religious Education Students in the Era of Social Media - Nurul Azizah; Falah Aulia Sani; Khairunnisa Khairunnisa; Fan Kurniawati Sukma Bulan; Indi Maulida; Pitra Gosha Patriasya (Action Research Journal Indonesia (ARJI), 2025)
The rise of globalization and advancements in technology, particularly social media, have significantly influenced the lifestyle changes and social values among students of Islamic Religious Education (PAI). This study aims to explore how PAI students interpret and embody an Islamic lifestyle amid the intensifying currents of modernization and digitalization. Employing a descriptive qualitative approach, the research was conducted at the State Islamic University (UIN) Raden Intan Lampung, involving fourth- and sixth-semester PAI students as participants. Data were collected through social media activity observation and in-depth interviews using the snowball sampling technique. The data were analyzed using the Miles and Huberman interactive model. The findings reveal two main tendencies in expressing Islamic identity: first, Islamic lifestyle is used as a social symbol and personal branding on social media; second, it serves as a genuine expression of faith that is private and spiritual in nature. Furthermore, the study identifies a gap between the religious appearance presented on social media and personal religious practice. Students are also engaged in negotiating their religious identity within digital spaces, which often leads to internal conflict between the pursuit of social visibility and spiritual sincerity. This study highlights the importance of critical awareness among PAI students in managing their Islamic identity to remain authentic in the face of pervasive digital cultural influences.